«Ridurre li drammi all’esigenza». Il modello performativo dell’opera in musica dai libretti del ‘Fondo Bonamici’ della Biblioteca Marucelliana di Firenze: disseminazione e adattamenti (1600-1737) - Degl’Innocenti, Luca; Pagnini, Caterina (Drammaturgia, 2021)
The essay is a synthesis of a project financed by the University of Florence, focused on the dissemination processes of the Italian opera in the Baroque era. The original perspective of the research sees the libretto as a privileged witness of these ‘adjustments’, through the analysis of the witnesses related to the different occasions which can define the different ways of reception and adaptation of the staging practice and the dramaturgical structure.